Consumer protection over soft issues relating to online advertising in Malaysia / Nur Hidayah Ab Aziz - Ab Aziz, Nur Hidayah (2014)
The emergence of the Internet has been currently affecting a number of areas in the business world including advertising. The increase of online advertisements in recent years shows that online advertising has become the preferred choice of marketers to establish their brands to all-encompassing consumers regardless of location, age, and institution. While online advertising offers huge opportunities in business-to-consumer (B2C) activities, it triggers many complex issues which necessitate legislative interference in the perspective of consumer protection. The prevalent issues are soft issues which revolved around threats to personal values, safety, behaviour and economic decisions of the consumer, including indecent and obscene advertising contents, the superfluous use of women in advertisements, advertisements targeted at children, as well as soft issues relating to online advertising of medicines and medical services. Unlike advertising in the real world, the threats offered by online advertising are deemed greater due to the global nature of the Internet and its evolving infrastructure. Therefore, the law should work in parallel with the current Internet infrastructure in order to ensure that it can be applied to online advertising and tackle the emerging soft issues affecting the consumer. This paper reviews the prevalent soft issues and the extent to which the existing Malaysian laws are adequate in protecting consumers in Malaysia.